High-insulation recyclable aramid fiber reinforced composite material as well as preparation method and application thereof

The method of preparing epoxy resin and aramid fibers through dynamic borate covalent networks solves the problem of difficult recycling of aramid fiber reinforced composite materials, and realizes composite materials with high insulation performance and recyclability, meets the performance requirements of high-voltage electrical equipment and promotes its green and environmentally friendly development.

CN119751945AActive Publication Date: 2025-04-04TIANJIN UNIV +1

Patent Information

Application Number
CN202510049067.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The existing aramid fiber reinforced composite materials are difficult to recycle after decommissioning, resulting in waste of resources and high processing costs, and their application in high voltage electrical equipment is limited by the reduction of material performance after recycling.

Method used

Epoxy resin is prepared through a dynamic borate covalent network and combined with aramid fibers by vacuum impregnation to form a highly insulated recyclable aramid fiber reinforced composite material. The method includes cleaning and drying of aramid fibers, preparing epoxy resin and BDB curing agents, vacuum impregnation and high temperature curing, and ultimately achieving degradation of epoxy resin and recovery of aramid fibers through an alcohol solution.

Benefits of technology

The high insulation performance and recyclability of aramid fiber reinforced composite materials are achieved, and the mechanical strength before and after recycling remains stable, which can meet the insulation and mechanical performance requirements of high-voltage electrical equipment, and promotes its green and environmental protection and reuse in power equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751945A_ABST
    Figure CN119751945A_ABST
Patent Text Reader

Abstract

The invention discloses a high-insulation recyclable aramid fiber reinforced composite material as well as a preparation method and application thereof, and belongs to the technical field of high-voltage electrical equipment. Epoxy resin and a BDB curing agent are adopted to carry out vacuum impregnation on high-performance aramid fiber cloth, and high-temperature curing molding is carried out to prepare the recyclable aramid fiber reinforced composite material, and the prepared recyclable aramid fiber reinforced composite material has the characteristics of high interfacial shear strength and high insulation breakdown strength, and is suitable for dry-type high-voltage electrical equipment and parts. And moreover, the aramid fibers in the composite material can be efficiently recycled by utilizing a simple and mild alcoholic solution method. Before and after recovery, the intrinsic mechanical strength of the aramid fiber is kept consistent, and the composite material prepared from the recovered aramid fiber can still show good performance. By realizing efficient degradation of the epoxy resin and recycling of the high-performance aramid fiber, not only is the utilization efficiency of resources improved, but also the environmental pollution is reduced, and the method has important significance for continuously promoting green and low-carbon development of novel electrical equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-voltage electrical equipment, and in particular to a high-insulation recyclable aramid fiber reinforced composite material and a preparation method and application thereof. Background Art

[0002] Aramid fiber reinforced composite materials (AFRC) are widely used in aerospace, automotive industry, electrical engineering and other fields due to their high specific strength, excellent insulation performance and corrosion resistance. Among them, aramid fiber insulation rods are key components in ultra-high voltage gas insulated switchgear (GIS), which play the role of transmitting mechanical power for opening and closing between high and low potentials. Compared with traditional glass fiber reinforced composite materials, AFRC is light in weight and high in strength, which can reduce the weight of the circuit breaker operating mechanism by one third, which is of great significance to improving the breaking efficiency of GIS circuit breakers, reducing operating work and achieving miniaturization. With the continuous development of my country's ultra-high voltage transmission projects, the number of GIS intervals has increased rapidly, and a large number of aramid fiber reinforced composite equipment and components have been put into operation. Many electrical equipment that were put into use earlier or damaged by faults are about to face retirement.

[0003] However, the three-dimensional cross-linked network formed by traditional aramid fiber-reinforced composites after curing is highly irreversible, which makes the treatment process of retired power equipment extremely complicated and difficult. Existing methods mainly treat or recycle through mechanical crushing or high-temperature degradation, which not only wastes resources but also increases the cost of waste treatment. At the same time, aramid fiber itself is expensive, and traditional methods make it economically unsustainable and of low recycling value.

[0004] At present, there are few reports on recyclable aramid fiber reinforced composite materials. The existing recycling methods have limitations when applied to high-voltage electrical equipment. It is difficult to ensure that the composite materials are recyclable and have excellent insulation properties. In particular, the performance of the recycled materials is difficult to meet the special requirements of high-voltage electrical equipment, which seriously restricts its further application in the field of electrical equipment. In view of the above problems, it is necessary to develop a preparation method for high-insulation, recyclable aramid fiber reinforced composite materials, so as to achieve the recycling and reuse of composite fiber on the basis of not affecting the insulation performance of the material, and promote its sustainable development. Summary of the invention

[0005] The purpose of the present invention is to provide a highly insulating recyclable aramid fiber reinforced composite material and a preparation method and application thereof, so as to solve the above problems. The highly insulating recyclable aramid fiber reinforced composite material not only has excellent interface shear strength and insulation performance, and the insulation breakdown strength meets the requirements of high-voltage equipment, but also can realize the effective recycling of aramid fiber through alcohol solution. Before and after recycling, the mechanical strength of aramid fiber remains stable, which provides a good solution for the green environmental protection and reuse of aramid fiber reinforced composite materials in power equipment.

[0006] To achieve the above object, the present invention discloses a method for preparing a high-insulation recyclable aramid fiber reinforced composite material, comprising the following steps:

[0007] S1, washing the aramid fiber and drying it;

[0008] S2. preparing an environmentally friendly epoxy resin formulation system based on a dynamic borate covalent network to obtain an epoxy resin;

[0009] S3. Aramid fibers are vacuum impregnated with epoxy resin and cured at high temperature to synthesize recyclable aramid fiber reinforced composite materials.

[0010] Preferably, step S2 comprises the following steps:

[0011] S2-1, using 1,4-phenylenediboronic acid and 1-thioglycerol, a BDB curing agent, 2,2'-(1,4-phenylene)-bis[4-yl-1,3,2-dioxaborane], was prepared by dehydration condensation reaction;

[0012] S2-2, under magnetic stirring conditions at 80-100°C, mix the epoxy resin and BDB curing agent for 20-60 minutes;

[0013] S2-3, the mixed epoxy resin is placed in a vacuum drying oven for degassing for 10-30 minutes;

[0014] The epoxy resin in step S2-2 includes any one of bisphenol A epoxy resin, bisphenol F epoxy resin and multifunctional epoxy resin; the molar ratio of epoxy group in the epoxy resin to mercapto group in the BDB curing agent is 0.6-1.2;

[0015] The setting temperature of the vacuum drying oven is 80-100°C.

[0016] Preferably, step S3 specifically includes the following steps:

[0017] S3-1, maintaining the temperature of the aramid fiber treated in step S1 at 60-100°C;

[0018] S3-2, maintaining the temperature of the epoxy resin prepared in step S2 at 60-100° C.;

[0019] S3-3, laying the aramid fiber fabric in the mold and sealing the mold;

[0020] S3-4, injecting epoxy resin into the mold of S3-3 by vacuum impregnation method, placing the mold in a vacuum environment of 80-100°C for 15-30 minutes to fully infiltrate the aramid fiber fabric;

[0021] S3-5, heating the mold at 100-120° C. for 4-6 hours to obtain a cured aramid fiber fabric;

[0022] S3-6. The cured aramid fiber fabric is taken out from the mold and placed in a vacuum oven at a temperature of 130-170° C. for post-curing for 4-10 hours to obtain a recyclable aramid fiber reinforced composite material.

[0023] Preferably, step S2-1 specifically includes the following steps:

[0024] S2-1-1, mixing 1,4-phenylenediboronic acid and 1-thioglycerol in anhydrous ethanol until dissolved;

[0025] S2-1-2, mechanically stirring the mixed solution at a temperature of 20-30° C. and atmospheric pressure for 24-48 hours;

[0026] S2-1-3, after the reaction, the anhydrous ethanol is removed under reduced pressure to obtain the target white product, namely 2,2'-(1,4-phenylene)-bis[4-yl-1,3,2-dioxaborolane];

[0027] The amount of 1,4-phenylenediboronic acid substance is 120 mmol;

[0028] The amount of 1-thioglycerol substance was 240 mmol;

[0029] The mass ratio of 1,4-phenylenediboronic acid to 1-thioglycerol is 20:25.96.

[0030] The present invention also provides a high-insulation recyclable aramid fiber reinforced composite material prepared by the above-mentioned preparation method. The interfacial shear strength of the high-insulation recyclable aramid fiber reinforced composite material can be increased by 50-60% compared with the composite material prepared by traditional electrical epoxy resin, and the power frequency breakdown strength meets the insulation performance requirements of high-voltage electrical equipment.

[0031] Preferably, the high-insulation recyclable aramid fiber reinforced composite material is recycled by an alcohol solution method after use, comprising the following steps:

[0032] (1) immersing the recyclable aramid fiber reinforced composite material in an alcohol solution to degrade the epoxy resin to obtain treated aramid fiber, the immersion temperature is 100-120° C., and the immersion time is 1-6 hours;

[0033] (2) placing the aramid fiber in anhydrous ethanol for ultrasonic oscillation for 30-60 minutes, and then washing it in deionized water for ultrasonic oscillation for 30-60 minutes;

[0034] (3) The washed aramid fiber is placed in a vacuum drying oven and dried for 6-12 hours at a temperature of 60-80° C. to obtain recycled aramid fiber.

[0035] Recycled aramid fibers can be used to prepare composite materials, whose interface shear strength and insulation breakdown strength remain basically the same as before recycling, and can be used for the green and environmentally friendly development of dry high-voltage equipment.

[0036] Preferably, the alcohol solution in step (1) is any one of benzyl alcohol, ethylene glycol, propylene glycol and anhydrous ethanol, and the mass ratio of the alcohol solution to the recyclable aramid fiber reinforced composite material is 30-60.

[0037] The high-insulation recyclable aramid fiber reinforced composite material provided by the present invention has excellent insulation performance and mechanical strength, can replace traditional glass fiber reinforced composite materials, and is applied to dry-type high-voltage electrical equipment and its key components, such as insulating pull rods, insulating support tubes, composite cross arms, etc., to achieve the development needs of weight reduction, efficiency improvement, small size, light weight and green environmental protection.

[0038] Therefore, the present invention has the following beneficial effects:

[0039] (1) Since the epoxy matrix after BDB curing contains more hydroxyl groups, the matrix and the aramid fiber have good interface bonding properties, making its interface shear strength higher than that of the aramid fiber reinforced composite material prepared by the traditional epoxy system. When subjected to mechanical stress, the good interface bonding strength effectively transfers and disperses the stress between the resin and the fiber, thereby meeting the mechanical performance requirements of electrical equipment. At the same time, since the synthesized BDB curing agent contains rigid groups such as benzene rings, the power frequency breakdown strength of the prepared aramid fiber reinforced composite material is basically consistent with that of the composite material prepared by the traditional epoxy system, which can meet the insulation performance requirements of electrical equipment operation.

[0040] (2) The present invention achieves mild degradation of aramid fiber reinforced composite materials based on alcohol solution, which solves the problem that the degradation of epoxy resin in traditional composite materials usually requires a catalyst or is carried out in a strong alkali, strong acid and other environments. The present invention can achieve degradation of composite materials through dynamic borate covalent bond network rearrangement (ester exchange) under catalyst-free conditions, thereby effectively recovering high-performance aramid fibers. The intrinsic mechanical strength of the recycled aramid fibers is not affected. After the recycled aramid fibers are used to make composite materials again, their interfacial shear strength and power frequency breakdown strength are basically the same as before recycling, and can still meet the insulation requirements of electrical equipment operation, thereby achieving the recycling of high-performance aramid fibers.

[0041] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a flow chart of the preparation of the highly insulating recyclable aramid fiber reinforced composite material and the recycling of aramid fiber in the present invention;

[0043] Figure 2 This is a comparison chart of the interface shear strength between the highly insulating recyclable aramid fiber reinforced composite material prepared in Example 1 of the present invention and the composite material prepared by the traditional electrical epoxy system;

[0044] Figure 3 This is a comparison chart of the power frequency breakdown strength of the interface between the highly insulating recyclable aramid fiber reinforced composite material prepared in Example 1 of the present invention and the composite material prepared by the traditional electrical epoxy system;

[0045] Figure 4 is a graph showing the morphological changes during the aramid fiber recovery process in Example 1 of the present invention;

[0046] Figure 5 1 is a microscopic morphology SEM image of the aramid fiber of Example 1 of the present invention, wherein a is a microscopic morphology SEM image of the unused aramid fiber, and b is a microscopic morphology SEM image of the recycled aramid fiber;

[0047] Figure 6 is a comparison chart of the intrinsic tensile strength of the recycled aramid fiber and the unused aramid fiber in Example 1 of the present invention;

[0048] Figure 7 is a comparison chart of the interfacial shear strength of the composite material prepared from the recycled aramid fiber and the unused aramid fiber in Example 1 of the present invention;

[0049] Figure 8 It is a comparison chart of the power frequency breakdown strength of the composite material prepared from the recycled aramid fiber and the unused aramid fiber in Example 1 of the present invention. DETAILED DESCRIPTION

[0050] The technical solution of the present invention is further illustrated by examples below.

[0051] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0052] In addition, it should be understood that although this specification is described according to the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.

[0053] like Figure 1 As shown, the present invention provides a method for preparing a highly insulating recyclable aramid fiber reinforced composite material and a method for recycling aramid fibers in the composite material.

[0054] The preparation method is as follows:

[0055] S1. Wash the aramid fiber and dry it.

[0056] S2. preparing an environmentally friendly epoxy resin formulation system based on a dynamic borate covalent network to obtain an epoxy resin;

[0057] S3. Aramid fibers are vacuum impregnated with epoxy resin and cured at high temperature to synthesize recyclable aramid fiber reinforced composite materials.

[0058] Step S2 includes the following steps:

[0059] S2-1. Using 1,4-phenylenediboronic acid and 1-thioglycerol, a BDB curing agent, namely 2,2'-(1,4-phenylene)-bis[4-yl-1,3,2-dioxaborane], is prepared by a dehydration condensation reaction.

[0060] S2-2. Mix the epoxy resin and BDB curing agent under magnetic stirring conditions at 80-100°C for 20-60 minutes.

[0061] S2-3. Place the mixed epoxy resin in a vacuum drying oven for 10-30 minutes to degas.

[0062] The epoxy resin in step S2-2 includes but is not limited to bisphenol A epoxy resin, bisphenol F epoxy resin and multifunctional epoxy resin; the molar ratio of the epoxy group in the epoxy resin to the mercapto group in the BDB curing agent is 0.6-1.2.

[0063] The setting temperature of the vacuum drying oven is 80-100°C.

[0064] Step S3 specifically includes the following steps:

[0065] S3-1. Maintain the temperature of the aramid fiber treated in step S1 at 60-100°C.

[0066] S3-2, maintaining the temperature of the epoxy resin prepared in step S2 at 60-100°C.

[0067] S3-3, laying the aramid fiber fabric in the mold and sealing the mold.

[0068] S3-4, inject epoxy resin into the mold of S3-3 by vacuum impregnation method, and place the mold in a vacuum environment of 80-100°C for 15-30 minutes to fully infiltrate the aramid fiber fabric.

[0069] S3-5. Heat the mold at 100-120° C. for 4-6 hours to obtain a cured aramid fiber fabric.

[0070] S3-6. The cured aramid fiber fabric is taken out from the mold and placed in a vacuum oven at a temperature of 130-170° C. for post-curing for 4-10 hours to obtain a recyclable aramid fiber reinforced composite material.

[0071] Step S2-1 specifically includes the following steps:

[0072] S2-1-1, mixing 1,4-phenylenediboronic acid and 1-thioglycerol in anhydrous ethanol until dissolved;

[0073] S2-1-2, mechanically stirring the mixed solution at a temperature of 20-30° C. and atmospheric pressure for 24-48 hours;

[0074] S2-1-3, after the reaction, the anhydrous ethanol is removed under reduced pressure to obtain the target white product, namely 2,2'-(1,4-phenylene)-bis[4-yl-1,3,2-dioxaborolane];

[0075] The amount of 1,4-phenylenediboronic acid substance is 120 mmol;

[0076] The amount of 1-thioglycerol substance was 240 mmol;

[0077] The mass ratio of 1,4-phenylenediboronic acid to 1-thioglycerol is 20:25.96.

[0078] The method for recycling aramid fibers in composite materials comprises the following steps:

[0079] (1) The recyclable aramid fiber reinforced composite material is immersed in an alcohol solution to achieve degradation of the epoxy resin to obtain the treated aramid fiber, the immersion temperature is 100-120° C., and the immersion time is 1-6 hours.

[0080] (2) The aramid fibers are ultrasonically vibrated in anhydrous ethanol for 30-60 min, and then washed in deionized water for 30-60 min.

[0081] (3) The washed aramid fiber is placed in a vacuum drying oven and dried for 6-12 hours at a temperature of 60-80° C. to obtain recycled aramid fiber.

[0082] The alcohol solution in step (1) includes but is not limited to benzyl alcohol, ethylene glycol, propylene glycol, and anhydrous ethanol, and the mass ratio of the alcohol solution to the recyclable aramid fiber reinforced composite material is 30-60.

[0083] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0084] Example 1

[0085] This embodiment provides a method for preparing a highly insulating recyclable aramid fiber reinforced composite material and a method for recycling aramid fibers, wherein steps 1-4 below are the preparation method, and steps 5-8 are the method for recycling aramid fibers.

[0086] Step 1: First, heat and clean the aramid fiber in a 100°C deionized water bath for 4 hours, then ultrasonically clean it with anhydrous ethanol for 1 hour, and finally dry it in a 60°C oven for 6 hours.

[0087] Step 2: Dissolve 120 mmol of 1,4-phenylenediboronic acid and 240 mmol of 1-thioglycerol in anhydrous ethanol at a mass ratio of 20:25.96, and mechanically stir the solution at 25° C. and atmospheric pressure for 30 hours. After the reaction, remove the anhydrous ethanol under reduced pressure to obtain the target white solid product, i.e., 2,2'-(1,4-phenylene)-bis[4-yl-1,3,2-dioxaborane] (BDB).

[0088] Step 3: Mix bisphenol A epoxy resin and BDB curing agent under magnetic stirring at 100° C., wherein the molar ratio of epoxy group in the epoxy resin to mercapto group in the BDB curing agent is 1.0; the stirring time is 30 minutes. The mixed epoxy resin is placed in a vacuum drying oven at 100° C. for 20 minutes for degassing.

[0089] Step 4, using vacuum impregnation and high temperature curing process to obtain a recyclable aramid fiber reinforced composite material. In this step, the temperature of the aramid fiber cloth treated in step 1 is maintained at 100°C, and the temperature of the epoxy resin prepared in step 3 is maintained at 100°C. Lay the aramid fiber fabric in the mold, seal the mold, inject the resin into the closed mold by vacuum impregnation, and place the mold in a vacuum environment at 100°C for 20 minutes to fully infiltrate it. Heat the mold at 100°C for 5 hours to cure it. Finally, take the sample out of the mold and place it in a vacuum oven at a temperature of 150°C for post-curing for 8 hours to obtain a highly insulating recyclable aramid fiber reinforced composite material.

[0090] Step 5: Immerse the high-insulation recyclable aramid fiber reinforced composite material in an ethylene glycol solution to degrade the epoxy resin, thereby obtaining treated aramid fiber, wherein the mass ratio of the ethylene glycol solution to the recyclable aramid fiber reinforced composite material is 40. The immersion temperature is 100° C., and the immersion time is 5 hours.

[0091] Step 6: The aramid fiber obtained by the above treatment is placed in anhydrous ethanol for ultrasonic oscillation for 50 minutes, and then washed in deionized water for ultrasonic oscillation for 50 minutes.

[0092] Step 7: Place the washed aramid fiber in a vacuum drying oven and dry it for 10 hours at a temperature of 60° C. to obtain recycled aramid fiber.

[0093] Step 8: Re-prepare the composite material using the recycled aramid fiber.

[0094] like Figure 2 as well as Figure 3 As shown, the interfacial shear strength of the highly insulating recyclable aramid fiber reinforced composite material prepared in this embodiment is 45.53MPa, while the interfacial shear strength of the composite material prepared by the conventional electrical epoxy system is 29.16MPa. For the power frequency breakdown strength, the composite material prepared by the recyclable epoxy system is 25.87kV / mm, while the composite material prepared by the conventional electrical epoxy system is 27.96kV / mm. From this, it can be concluded that the interfacial shear strength of the composite material prepared by the recyclable epoxy system is increased by 56.14% compared to the composite material prepared by the conventional electrical epoxy system, while the power frequency breakdown strength of the two is not much different.

[0095] like Figure 4 As shown in the figure, the highly insulating recyclable aramid fiber reinforced composite material is immersed in ethylene glycol solution. At 120°C, as the immersion time increases, the epoxy resin gradually dissolves. After immersion for 10 minutes, it can be observed that the epoxy resin is partially dissolved and the solution gradually becomes turbid; when the immersion time reaches 90 minutes, the epoxy resin is almost completely dissolved, and the recycled aramid fiber is obtained.

[0096] like Figure 5 As shown, by comparing the SEM images of the fiber surfaces of the recycled aramid fiber in this embodiment with those of the unused aramid fiber, it can be seen that the surface of the unused aramid fiber is relatively smooth, and the surface of the recycled aramid fiber is clean with basically no resin residue.

[0097] like Figure 6 As shown in the figure, the intrinsic tensile strength of the recycled aramid fiber in this embodiment is compared with that of the unused aramid fiber. The intrinsic tensile strength of the unused aramid fiber is 690.85 MPa, while the intrinsic tensile strength of the recycled aramid fiber is 762.96 MPa. From this result, it can be concluded that after recycling, the intrinsic tensile strength of the aramid fiber is increased by 10.44%.

[0098] like Figure 7 as well as Figure 8 As shown in the figure, the interface shear strength of the composite material prepared by the initial use of unused aramid fiber is 45.51MPa, while the interface shear strength of the composite material prepared by the recycled aramid fiber is 47.05MPa. In addition, the power frequency breakdown strength of the composite material prepared by the initial use of unused aramid fiber is 26.37kV / mm, and the power frequency breakdown strength of the recycled composite material is 31.70kV / mm. From this result, it can be concluded that after recycling, the interface shear strength and power frequency breakdown strength of the composite material are basically the same as before recycling or even improved. This is because the surface activity of the fiber is enhanced after the secondary treatment, which improves its interface bonding with the matrix.

[0099] Example 2

[0100] This embodiment provides a method for preparing a highly insulating recyclable aramid fiber reinforced composite material and a method for recycling aramid fibers, wherein steps 1-4 below are the preparation method, and steps 5-8 are the method for recycling aramid fibers.

[0101] Step 1: First, heat and clean the aramid fiber in deionized water at 100°C for 4 hours, then ultrasonically clean it with anhydrous ethanol for 1 hour, and finally dry it in an oven at 60°C for 6 hours.

[0102] Step 2: Dissolve 120 mmol of 1,4-phenylenediboronic acid and 240 mmol of 1-thioglycerol in anhydrous ethanol at a mass ratio of 20:25.96, and mechanically stir the solution at 20° C. and atmospheric pressure for 45 hours. After the reaction, remove the anhydrous ethanol under reduced pressure to obtain the target white solid product, i.e., 2,2'-(1,4-phenylene)-bis[4-yl-1,3,2-dioxaborane] (BDB).

[0103] Step 3: Mix bisphenol A epoxy resin and BDB curing agent under magnetic stirring at 90° C., wherein the molar ratio of epoxy group in the epoxy resin to mercapto group in the BDB curing agent is 1.1; the stirring time is 40 minutes. The mixed epoxy resin is placed in a vacuum drying oven at 100° C. for 25 minutes for degassing.

[0104] Step 4, using vacuum impregnation and high temperature curing process to obtain a recyclable aramid fiber reinforced composite material. In this step, the temperature of the aramid fiber cloth treated in step 1 is maintained at 80°C, and the temperature of the epoxy resin prepared in step 3 is maintained at 80°C. Lay the aramid fiber fabric in the mold, seal the mold, inject the resin into the closed mold by vacuum impregnation, and place the mold in a vacuum environment at 80°C for 25 minutes to fully infiltrate it. Heat the mold at 110°C for 6 hours to cure. Finally, take the sample out of the mold and place it in a vacuum oven at 160°C for post-curing for 6 hours to obtain a highly insulating recyclable aramid fiber reinforced composite material.

[0105] Step 5: Immerse the highly insulating recyclable aramid fiber reinforced composite material in a propylene glycol solution to degrade the epoxy resin, thereby obtaining treated aramid fiber, wherein the mass ratio of the propylene glycol solution to the recyclable aramid fiber reinforced composite material is 50. The immersion temperature is 110° C., and the immersion time is 4 hours.

[0106] Step 6: The aramid fiber obtained by the above treatment is placed in anhydrous ethanol for ultrasonic oscillation for 40 minutes, and then washed in deionized water for ultrasonic oscillation for 40 minutes.

[0107] Step 7: Place the washed aramid fiber in a vacuum drying oven and dry it for 8 hours at a temperature of 70° C. to obtain recycled aramid fiber.

[0108] Step 8: Re-prepare the composite material using the recycled aramid fiber.

[0109] In summary, the present invention provides a highly insulating recyclable aramid fiber reinforced composite material and a preparation method and application thereof. The power frequency breakdown strength of the highly insulating recyclable aramid fiber reinforced composite material is basically consistent with that of the composite material prepared by the traditional epoxy system, and can meet the insulation performance requirements of electrical equipment operation. In addition, the mild degradation of the aramid fiber reinforced composite material is achieved by using an alcohol solution, thereby effectively recovering high-performance aramid fibers, and the intrinsic mechanical strength of the aramid fibers before and after recovery remains stable. After the recycled aramid fibers are used to make a composite material again, the interfacial shear strength and power frequency breakdown strength thereof are basically consistent with those before recovery, and can still meet the insulation requirements of electrical equipment operation, thereby realizing the recycling of high-performance aramid fibers.

[0110] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a highly insulating recyclable aramid fiber reinforced composite material, characterized in that: The following steps are involved: S1, washing the aramid fiber and drying it; S2. preparing an environmentally friendly epoxy resin formulation system based on a dynamic borate covalent network to obtain an epoxy resin; S3. Aramid fibers are vacuum impregnated with epoxy resin and cured at high temperature to synthesize recyclable aramid fiber reinforced composite materials.

2. The method for preparing a highly insulating recyclable aramid fiber reinforced composite material according to claim 1, characterized in that: Step S2 includes the following steps: S2-1, using 1,4-phenylenediboronic acid and 1-thioglycerol, a BDB curing agent is prepared by a dehydration condensation reaction, namely 2,2'-(1,4-phenylene)-bis[4-yl-1,3,2-dioxaborane]; S2-2, under magnetic stirring conditions at 80-100°C, mix the epoxy resin and BDB curing agent for 20-60 minutes; S2-3, placing the mixed epoxy resin in a vacuum drying oven for degassing for 10-30 minutes; The epoxy resin in step S2-2 includes any one of bisphenol A epoxy resin, bisphenol F epoxy resin and multifunctional epoxy resin; the molar ratio of epoxy group in the epoxy resin to mercapto group in the BDB curing agent is 0.6-1.2; The setting temperature of the vacuum drying oven is 80-100°C.

3. The method for preparing a highly insulating recyclable aramid fiber reinforced composite material according to claim 1, characterized in that: Step S3 specifically includes the following steps: S3-1, maintaining the temperature of the aramid fiber treated in step S1 at 60-100°C; S3-2, maintaining the temperature of the epoxy resin prepared in step S2 at 60-100° C.; S3-3, laying the aramid fiber fabric in the mold and sealing the mold; S3-4, injecting epoxy resin into the mold of S3-3 by vacuum impregnation method, placing the mold in a vacuum environment of 80-100°C for 15-30 minutes to fully infiltrate the aramid fiber fabric; S3-5, heating the mold at 100-120° C. for 4-6 hours to obtain a cured aramid fiber fabric; S3-6. The cured aramid fiber fabric is taken out from the mold and placed in a vacuum oven at a temperature of 130-170° C. for post-curing for 4-10 hours to obtain a recyclable aramid fiber reinforced composite material.

4. The method for preparing a highly insulating recyclable aramid fiber reinforced composite material according to claim 2, characterized in that: Step S2-1 specifically includes the following steps: S2-1-1, mixing 1,4-phenylenediboric acid and 1-thioglycerol in anhydrous ethanol until dissolved, the mass ratio of 1,4-phenylenediboric acid to 1-thioglycerol being 20:25.96; S2-1-2, mechanically stirring the mixed solution at a temperature of 20-30° C. and atmospheric pressure for 24-48 hours; S2-1-3. After the reaction, the anhydrous ethanol is removed under reduced pressure to obtain the target white product, namely 2,2'-(1,4-phenylene)-bis[4-yl-1,3,2-dioxaborolane].

5. A highly insulating recyclable aramid fiber reinforced composite material, characterized in that: The composite material is prepared by the method for preparing the highly insulating recyclable aramid fiber reinforced composite material according to any one of claims 1 to 4.

6. The high insulation recyclable aramid fiber reinforced composite material according to claim 5, characterized in that: The high-insulation recyclable aramid fiber reinforced composite material is recycled by an alcohol solution method after use. The recycling method includes the following steps: (1) immersing the recyclable aramid fiber reinforced composite material in an alcohol solution to degrade the epoxy resin to obtain treated aramid fiber, the immersion temperature is 100-120° C., and the immersion time is 1-6 hours; (2) placing the aramid fiber in anhydrous ethanol for ultrasonic oscillation for 30-60 minutes, and then washing it in deionized water for ultrasonic oscillation for 30-60 minutes; (3) The washed aramid fiber is placed in a vacuum drying oven and dried for 6-12 hours at a temperature of 60-80° C. to obtain recycled aramid fiber.

7. The high insulation recyclable aramid fiber reinforced composite material according to claim 6, characterized in that: The alcohol solution in step (1) is any one of benzyl alcohol, ethylene glycol, propylene glycol and anhydrous ethanol, and the mass ratio of the alcohol solution to the recyclable aramid fiber reinforced composite material is 30-60.

8. An application of the highly insulating recyclable aramid fiber reinforced composite material as claimed in claim 5, characterized in that: Highly insulating recyclable aramid fiber reinforced composites are used in dry-type high-voltage electrical equipment and their key components.

Citation Information

Patent Citations

  • High-performance recyclable and easy-to-repair epoxy resin and preparation method thereof

    CN112608452A

  • Fluffy light filament bamboo fiber forming curing additive and preparation method thereof

    CN117624836A

  • Preparation method of recoverable and easy-to-repair epoxy resin as well as product and recovery process thereof

    CN118852586A

  • Recyclable epoxy resin matrix and preparation method thereof, composite material and preparation method thereof

    CN119220058A

  • A slow reacting recyclable epoxy resin system for structural composites

    US20230295414A1

Cited By

  • Recycling method and application of meta-position aramid fiber material

    CN120842680A